The Place of Monetary Policy in the Stabilization Program - Chandler, Lester V. (The Review of Economics and Statistics, 1951)
cumulate. But a simpler solution may well be heavier taxes and compulsory loans (i.e., taxloans). These, together with income control and, where necessary, adequate price and supply controls, may keep the supply of money in check and induce additional demand for money for holding. Only in so far as the seriousness of the world situation does not justify generous use of controls and the liquidity problem continues to threaten stability, would special incentives to non-banking lenders be justified. In short, we should seek help in the fight against inflation wherever it can be had; but we are not optimistic concerning the contribution likely to be had from monetary policy. In the present (Spring, I951) state of the world crisis, we should depend primarily on fiscal policy and secondarily on limited income and other controls. Monetary policy may be helpful, but as the crisis deepens it is likely, as in the past emergencies, to become increasingly passive. In this discussion, I have not dealt with the restraints on monetary expansion exercised through controls of particular types of loans, or even rationing of total loans or freezes on the amount outstanding. These, in fact, belong to the category of direct controls and not to general monetary control operating through changes in the price of money.